CGRP pathway monoclonal antibodies for cluster headache. (2nd August 2020) - Chan, Calvin; Goadsby, Peter J.
ABSTRACT: Introduction: The involvement of the calcitonin gene-related peptide (CGRP) pathway in primary headache disorders, especially migraine, had led to recent success in the development of new migraine therapies. The CGRP pathway also plays a role in the pathophysiology of cluster headache, so CGRP pathway monoclonal antibodies have been studied in the prevention of cluster headache attacks. Areas covered: This review will outline the trials of fremanezumab and galcanezumab, the two CGRP pathway monoclonal antibodies that have undergone trials in cluster headache prevention. This review will highlight key efficacy and safety outcomes from the trials. Expert opinion: Galcanezumab was shown to be efficacious, reducing the frequency of attacks in episodic cluster headache, while fremanezumab failed its primary endpoint in episodic cluster headache. Both fremanezumab and galcanezumab trials in chronic cluster headache were terminated after futility analysis predicting the failure of both trials to fulfil their primary endpoint. The role of CGRP in cluster headache supports ongoing trials of the remaining CGRP pathway monoclonal antibodies and gepants for preventive and acute treatment. A broad view would include targeting neuropeptides involved in parasympathetic signaling in cluster headache, such as pituitary adenylate cyclase-activating peptide (PACAP); such targets warrant exploration in the search of new treatments.